(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Background : Drug of abuse is a global predicament. The cases of drug abuse among youths is shooting up day by day. Individuals who are addict to narcotic and psychoactive drugs hamper their mental and physical wellbeing, which eventually mirrors into their personality. Aim: The objective of the study was to assess behavioral changes in drugs addicts. Method: 16 personality factor questionnaire was used to get responses from victims. These responses were then converted into score using 16 PF manual. Results: The present study deals with the assessment of behavioral traits of drug victims. A 16 personality factor questionnaire was used to evaluate traits of addicts of stimulant drugs like nicotine, cocaine and psychoactive substances like cannabis. Output recorded was converted from raw score to sten score. A graph was plotted to represent various behavioral traits. Conclusion: The results suggests that majority of drug addicts turn out to be reserved, undisciplined, the intelligence is affected and are strongly affected by feelings which reveals a strong connection between drugs and their persistently mutating behavioral aspects which eventually drags them towards getting involved into crime.